Penerapan Manajemen Risiko Event Dalam Meminimalisir Human Error Di Esmeralda Wedding Planner & Organizer - Sari, Rochpina Cantika; Suprastayasa, I Gusti Ngurah Agung; Ariasri, Nyoman Reni (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This study aims to determine how the implementation of event risk management minimizes human error at Esmeralda Wedding Planner & Organizer. This study uses a qualitative descriptive approach with data collection techniques in the form of interviews, observations, and documentation studies conducted at Esmeralda Wedding Planner & Organizer. Data analysis was carried out using an approach based on ISO 31000: 2018 which consists of seven systematic stages, namely: communication and consultation, context determination, risk identification, risk analysis, risk evaluation, risk handling, and monitoring and review. The results of the study indicate that Esmeralda Wedding Planner & Organizer has implemented all stages of risk management well and in a structured manner. Efforts made include conducting briefings before the event, routine weekly evaluations, preparing clear job descriptions, implementing SOPs, and imposing social sanctions or blacklisting on employees who violate. This study is expected to be a reference for event industry players, especially wedding organizers, in increasing work effectiveness and managing risks more professionally.